2021
DOI: 10.1159/000514552
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet Therapy after Intracerebral Hemorrhage and Subsequent Clinical Events: A 12-Year South Korean Cohort Study

Abstract: <b><i>Introduction:</i></b> Antiplatelet agents are usually discontinued to reduce hemorrhagic tendency during the acute phase of intracerebral hemorrhage (ICH). However, their use after ICH remains controversial. <b><i>Methods:</i></b> This study investigated the effect of antiplatelet agents in ICH survivors. We used the National Health Insurance Service-National Sample Cohort 2002–2013 database for retrospective cohort modeling, estimating the effects of antip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…These findings alongside published observational studies provide reassurance about the use of long-term antiplatelet therapy after ICH associated with antithrombotic therapy. Since RESTART’s main results were published, 1 stroke guideline has recommended, “In patients with an indication for continued antiplatelet treatment, resuming antiplatelet therapy is reasonable (Evidence Level B).” However, we did not observe a change in participants’ adherence during extended follow-up after the main results were published, so patients and guidelines will require greater strength and certainty of evidence to change clinical practice.…”
Section: Discussionsupporting
confidence: 52%
“…These findings alongside published observational studies provide reassurance about the use of long-term antiplatelet therapy after ICH associated with antithrombotic therapy. Since RESTART’s main results were published, 1 stroke guideline has recommended, “In patients with an indication for continued antiplatelet treatment, resuming antiplatelet therapy is reasonable (Evidence Level B).” However, we did not observe a change in participants’ adherence during extended follow-up after the main results were published, so patients and guidelines will require greater strength and certainty of evidence to change clinical practice.…”
Section: Discussionsupporting
confidence: 52%
“…The results revealed that restarting APT after ICH reduced the occurrence of primary outcome events (nonfatal ICH recurrence, nonfatal ischemic stroke, nonfatal myocardial infarctions; adjusted HR 0.743, 95% CI 0.578–0.956) and all‐cause mortality (adjusted HR 0.740, 95% CI 0.552–0.991) without increasing the risk of recurrent ICH, especially in patients without prior APT. 89 Weimar et al 90 and Viswanathan et al 91 further supported this finding, demonstrating that the usage of antiplatelet medications following ICH treatment in patients was not linked to recurrent ICH. Furthermore, a comprehensive review that included data from nine randomized trials revealed that the overall OR of recurrent ICH in patients taking antithrombotic treatment was 1.00 (95% CI 0.73–1.37, p = 1).…”
Section: Reinitiate Apt Post‐ Ichmentioning
confidence: 87%
“…Moon et al followed up on ICH survivors with clinical events for 12 years. The results revealed that restarting APT after ICH reduced the occurrence of primary outcome events (nonfatal ICH recurrence, nonfatal ischemic stroke, nonfatal myocardial infarctions; adjusted HR 0.743, 95% CI 0.578–0.956) and all‐cause mortality (adjusted HR 0.740, 95% CI 0.552–0.991) without increasing the risk of recurrent ICH, especially in patients without prior APT 89 . Weimar et al 90 and Viswanathan et al 91 further supported this finding, demonstrating that the usage of antiplatelet medications following ICH treatment in patients was not linked to recurrent ICH.…”
Section: Reinitiate Apt Post‐ichmentioning
confidence: 98%
“…13 However, in clinical practice, only 5% of patients received antiplatelet therapy within 1 month after ICH. 14 To date, there is no recommendation regarding the appropriate time interval between the presentation of ICH and the resumption of antiplatelet. Using the national cohort database in Taiwan, the aim of this study was to compare the safety outcome between early (≤30 days) and late (31-365 days) antiplatelet resumption in ICH survivors to fill this gap.…”
Section: See Related Article P 546mentioning
confidence: 99%